THE INFLUENCE OF COLLABORATIVE TEACHING TOWARD GRADUATE STUDENTS’ TEAMWORK CAPACITY - Muhammad, Asrori; Chairil Effendy, (Advances in Social Sciences Research Journal, 2022)
The objective of this research is to reveal the influence of collaborative teaching toward graduate students’ teamwork capacity, including four aspects, which are: sharing, collaboration, concern to rights and welfare of others, and caring to others. This quasi experimental study was conducted with one group pretest-posttest design. There are 38 graduate students of guidance and counseling department as research subjects. Collecting data was conducted by following a Collaborative Teamwork Inventory. The profile of graduate students’ teamwork capacity was analyzed by comparing between actual score and maximal ideal score based on the nomal curve. The effect of collaborative teaching toward students’ capacity was analyzed by a t-test for paired samples. The findings indicated that collaborative teaching was effective to increase students’ teamwork capacity. It was proven that pretest score tend to move towards the “lower level” whereas the posttest score tend to shift to a “higher level.” The analysis of t-test for paired samples indicated that t = -26.69 and p= .000. It does mean that collaborative teaching influenced significantly towards the improvement of students’ teamwork capacity.